The Environmental Roles in Song Lyrics of Michael Jackson's "Earth Song" And Lil Dicky's "Earth": An Eco Critical Analysis - Karwur, Vieren Gloryan; Rorintulus, Olga; Lolowang, Imelda (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
The purpose of this research is to describe the role of the natural environment in the lyrics of Michael Jackson's "EARTH SONG" (1995) and Lil Dicky's "EARTH" (2019). The data is taken from the two song lyrics. This research uses qualitative methods and eco critical theory from Cheryl Goltfelty. The primary source is the song lyrics of Michael Jackson's "EARTH SONG" (1995) and Lil Dicky's "EARTH" (2019). Secondary sources are articles, websites, and journals discussing the natural environment related to this research. The results of this research are that the first is the role of the natural environment reflected in the lyrics of the songs, namely the role of habitat, which is very important for living things in the form of forests, grasslands, and the sea. And the role of Population regulation, the environment plays a role in regulating the number of individuals in the population of a species. Nutrients and energy, the environment provides the energy and material resources necessary for organisms to perform their life functions.; second is the impact of natural destruction reflected in the song lyrics, namely that natural destruction causes human suffering, including climate change and loss of biodiversity, as well as hunger, poverty, and social conflict; and third is the comparison of environmental representations of the two song lyrics, namely both songs emphasize the importance of protecting the earth and have strong messages about the adverse effects of human activities on the environment.